The Jay’s wing by Ivan Franko: imaginary drama dialogue - Virchenko, Tetiana (2021)
In accordance with European tendencies, modernization penetrated the Ukrainian culture as an “artistic philosophy” (by S. Pavlychko). Ivan Franko, as an artist and thinker, underwent several evolutionary changes during his life. The modernist artistic heritage of I. Franko existed in the context of the works of Lesia Ukrainka, O. Kobylyanska, V. Stefanyk, M. Kotsyubynsky and M. Cheremshyna. But in the literary debate, Franko remained a staunch opponent of those who urged Ukrainian writers to abandon realism. I. Franko’s short story The Jay’s wing. From the notes of a hermit is an experiment of literary form. We aim to analyze various aspects of this literary phenomenon, which will clarify the Ivan Franko's role in the process of Ukrainian literature modernization. This short story does not provide a lot of material for the classical narratological method. Therefore, it makes sense to combine it with psychological interpretation and semiotic observations. One of the directions of expanding the possibilities of semiotic interpretation through narrative observations is the involvement of the conceptual sphere of cinematic poetics.